Spatial distribution of bats richness in Mexico at different taxonomic levels: biogeographical and conservation implications - Barrios-Gómez, Kinberly Montserrat; Lopez-Wilchis, Ricardo; Díaz-Larrea, Jhoana; Guevara-Chumacero, Luis Manuel (THERYA, 2019)
Due to the potential of bats to travel long distances, the great diversity of habitats in which they are found, and their biological peculiarities, bats typically have been excluded in biogeographic analyses. However, like other mammals, bats show common distributional patterns strongly influenced by their biotic and abiotic interactions, aspects that have been poorly analyzed mainly due to technical and methodological limitations. Such occurrence data are limited to a subset of a species’ range, the scale of occurrence records, characteristics of the life history (e.g., territory size, vagility) of the taxa being studied, and issues of environmental variable selection and, therefore, the modeling methods and the evaluation of them. In this work, the objectives were to: 1) Evaluate the spatial variation in bat richness in Mexico, both for the order as a whole and at the family taxonomic level. 2) Quantify overlapping species occurrences and corresponding richness values in order to statistically model and generate bat richness maps at different taxonomic levels. 3) Explore the relationship of bat richness with environmental factors and with the biogeographic regions proposed for Mexico. 4) Identify areas of interest with high richness. The information available on the Global Biodiversity Information Facility database for bat species with distribution in Mexico was downloaded, and clearly erroneous records deleted. Using the Kriging Ordinary utility (KO), inside the QGIS software, a geostatistical analysis interpolation data was used to determine patterns of richness. The relationship of bat richness to climate, vegetation, and the biotic provinces proposed for Mexico was also explored. Spatial variation in richness was evaluated at the taxonomic levels of order and family. Based on this determination, areas of interest were identified for their high richness. When considering all species of bats the highest diversity is in the central part of the West, the Northeast zone and on both sides of the Isthmus of Tehuantepec. However, there are differences present at the family level. Deciduous tropical forest vegetation type presents high bat richness, followed by pine-oak forest and evergreen tropical forest. Temperate sub-humid, warm sub-humid and warm-humid climate types correspond to the highest bat richness of both order and family. Collection localities are not uniformly distributed over the country, most of them being concentrated in the west, east and south of the country, while there are very few records in the north and central plateau, and this is reflected in the richness concentration per cell (values from 0 to 52 species per cell). Protection of the four areas with an overall high concentration of bat richness detected in this analysis should be a priority during the development of conservation strategies.